Modeling and Control of Inverter Zero-Voltage-Switching for Inductive Power Transfer System - Jiangtao Liu; Qijun Deng; Wenbin Wang; Zhifan Li (IEEE Access, 2019)
It's very important to maintain the inverter zero-voltage-switching(ZVS) for inductive power transfer (IPT) system, especially for those high power applications. The ZVS condition can be obtained via regulating the inverter operating frequency of the IPT system. A modeling method based on the energy-amplitude and phase is proposed and corresponding controller is designed to maintain the inverter ZVS condition for IPT. The dynamic model of the ZVS for the half-bridge inverter is developed firstly. To facilitate the dynamic performance analysis and controller design, the original time-variant model is linearized with small-signal method at its operating point, which yields to a 4 order transfer function model. A PI controller which maintains ZVS condition via regulating the inverter operating frequency is designed based on the transfer function. An IPT prototype is built to verify the proposed theory. Experiments show that the controller traces the reference of the ZVS angle within 20 ms under various perturbation, which verifies the correction and effectiveness of the model and controller.